The Taricco saga and the consolidation of judicial dialogue in the European Union: CJEU, C-105/14 Ivo Taricco and others, ECLI:EU:C:2015:555; and C-42/17 M.A.S., M.B., ECLI:EU:C:2017:936 Italian Constitutional Court, Order no. 24/2017. Issue 3 (June 2018) - Bonelli, Matteo
In December 2017, the Court of Justice of the European Union delivered its awaited decision on the Taricco II case, responding to a preliminary reference from the Italian Corte Costituzionale . The latter, unhappy with the outcome of the earlier Taricco I decision, asked for a re-interpretation of Article 325 TFEU and threatened the Court of Justice with the possible activation of its controlimiti doctrine. The CJEU partially 'corrected' its previous ruling and prevented an open conflict between EU law and Italian constitutional law. This case note discusses the saga and its three episodes against the background of the growing constitutional conversation between top European courts. It argues that Taricco is a positive episode of judicial dialogue and may further contribute to its consolidation: on one hand, constitutional courts are increasingly willing to 'play the game' and refer to the CJEU under Article 267 TFEU; on the other, the Court of Justice seems more reactive than in the past to constitutional courts' claims and now considers them with increasing attention and detail. Finally, the case note reflects on the partially diverging languages for constitutional dialogue: national courts use the language of constitutional identity, while the CJEU prefers to refer to the 'common constitutional principles of the EU'.